Determinants of social media use for professional agricultural extension: a cross-sectional survey of practitioners in Limpopo Province, South Africa - Patience Manku Nkoana; Elliot Zwane; Abenet Belete (Talenta Publisher, 2026)
The increasing need for cost-effective and accessible communication in agricultural extension has driven the adoption of social media platforms. This study examined the use of social media platforms for professional extension work among agricultural extension practitioners in Limpopo Province, South Africa. A quantitative cross-sectional survey was conducted in 2025 among 225 extension practitioners selected through multistage random sampling from a population of 538. Data were collected using structured questionnaires and analysed using descriptive statistics and Pearson chi-square tests in SPSS version 30. The results showed that social media is widely used amongst extension practitioners. WhatsApp emerged as the dominant platform used by all respondents. On the other hand, platforms such as Facebook, YouTube, and TikTok are also used, but mainly for sharing visual and interactive content. Extension practitioners were more likely to access agricultural information on social media than to create original advisory content for their farmers. Text messages and voice notes were the most shared content types, reflecting the preference for simple, low-data communication formats. This preference is suitable for rural connectivity conditions and less expensive. A significant association was found between years of service and professional social media use. Factors like age, gender, qualification, and district showed no significant influence. The findings indicate that although social media has strong potential to enhance extension service delivery, it remains underutilised. The study highlights the need to strengthen digital skills, improve internet access, and develop guidelines for professional social media use.